2023
DOI: 10.1111/jgh.16174
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet and ethnicity on gut microbiota variation in irritable bowel syndrome: A multi‐center study

Abstract: Background and Aim:The gut microbiota in irritable bowel syndrome (IBS) is known to vary with diet. We aim to (i) analyze the gut microbiota composition of IBS patients from a multi-ethnic population and (ii) explore the impact of a low FODMAP diet on gastrointestinal symptoms and gut microbiota composition among IBS patients. Methods: A multi-center study of multi-ethnic Asian patients with IBS was conducted in two phases: (i) an initial cross-sectional gut microbiota composition study of IBS patients and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In a recent multicenter study amongst Asian IBS patients, Khoo et al . observed that poor adherence to the low‐FODMAP diet was prevalent amongst 51.7% of IBS subjects, despite regular monitoring by dietitians 7 . IBS patients with poorer adherence to a low FODMAP in this study had less symptom improvement (92.9% vs 46.7% symptom improvement between those with good vs poor adherence).…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…In a recent multicenter study amongst Asian IBS patients, Khoo et al . observed that poor adherence to the low‐FODMAP diet was prevalent amongst 51.7% of IBS subjects, despite regular monitoring by dietitians 7 . IBS patients with poorer adherence to a low FODMAP in this study had less symptom improvement (92.9% vs 46.7% symptom improvement between those with good vs poor adherence).…”
mentioning
confidence: 50%
“…In a recent multicenter study amongst Asian IBS patients, Khoo et al observed that poor adherence to the low-FODMAP diet was prevalent amongst 51.7% of IBS subjects, despite regular monitoring by dietitians. 7 IBS patients with poorer adherence to a low FODMAP in this study had less symptom improvement (92.9% vs 46.7% symptom improvement between those with good vs poor adherence). However, even amongst IBS patients with a reported poor adherence, 46.7% had symptom improvement, suggesting that factors other than adherence may have influenced the dietary intervention response.…”
mentioning
confidence: 53%
See 2 more Smart Citations